Keunggulan kompetitif bank syariah: Analisis strategi berbasis nilai sosial dan ekonomi islam - Aini, Kurrotul (Maliki Interdisciplinary Journal, 2025)
The development of the Islamic banking sector in Indonesia shows significant changes along with the increasing public understanding of fair and ethical financial principles. Amid increasingly complex global competition, the competitive strength of Islamic banks depends not only on financial efficiency, but also on their ability to align social values and Islamic economic principles with their business plans. This article explores how the aspects of Maqasid al-shariah, which include welfare, justice, and social sustainability, can form the foundation of a strategy for Islamic banks to create lasting uniqueness. The theoretical approach uses Porter’s five forces framework and SWOT analysis from an Islamic economic perspective to evaluate internal strengths, external opportunities, and competitive threats in the financial sector. The results of various studies show that strategies based on social values and Islamic economic principles can be a major source of competitive advantage for Islamic banks. There are three main ways in which these strategies work. First, Islamic banks build public trust through transparent practices and compliance with sharia principles. Second, Islamic banks utilize ethical digital innovation to expand their service reach and increase financial inclusion for various segments of society. Third, Islamic banks integrate social responsibility into their business activities, giving them a strong differentiator compared to conventional banks. In addition, the implementation of risk management in accordance with sharia principles helps strengthen the stability and reputation of the institution. Meanwhile, marketing strategies that promote religious values have been proven to foster customer loyalty.